A Prior Magazine 9. - Roelandt, Els; Pirotte, Phillippe; Wiarda, Andrea; Laermans, Rudi; Gielen, Pascal; Illegems, Paul (Brussel : vzw Mark, 2004)
de Bruyn, Goele ; Van Golden, Daan ; Durham, Jimmie
boek